Chronic cerebral hypoperfusion induces venous dysfunction via EPAS1 regulation in mice - Vanessa Kristina Wazny; Aparna Mahadevan; Nhi Nguyen; Hannah Wee; Ashwati Vipin; Tammy Lam; Kai Yi Tay; Jia-Xiang See; Gurveen Sandhu; Yi Jin Leow; Giuseppe D’Agostino; Martin Graf; et al. (Nature Communications)
Abstract Vascular dementia is the second most common form of dementia. Yet, the mechanisms by which cerebrovascular damage progresses are insufficiently understood. Here, we create bilateral common carotid artery stenosis in mice, which effectively impairs blood flow to the brain, a major cause of the disease. Through imaging and single-cell transcriptomics of the mouse cortex, we uncover that blood vessel venous cells undergo maladaptive structural changes associated with increased Epas1 expression and activation of developmental angiogenic pathways. In a human cell model comparing arterial and venous cells, we observe that low-oxygen condition leads to sustained EPAS1 signaling specifically in venous cells. EPAS1 inhibition reduces cerebrovascular abnormalities, microglial activation, and improves markers of cerebral perfusion in vivo. In human subjects, levels of damaged endothelial cells from venous vessels are correlated with white matter injury in the brain and poorer cognitive functions. Together, these findings indicate EPAS1 as a potential therapeutic target to restore cerebrovascular integrity and mitigate neuroinflammation.